Jordan : 2009 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Jordan. (IMF Staff Country Reports; Country Report, 2009)
This 2009 Article IV Consultation highlights that Jordan's money and financial markets have weakened since mid-2008. Bank deposits edged down slightly in October but subsequently recovered, with the share of dinar deposits continuing to increase. Executive Directors have noted that sound macroeconomic management has enhanced Jordan's resilience to the global crisis. Directors have also emphasized that, in light of the economy's close ties with the region and reliance on external financing, near-term policies should remain focused on guarding against vulnerabilities.